The Role of Ion Channels in Microglial Activation and Proliferation – A Complex Interplay between Ligand-Gated Ion Channels, K+ Channels, and Intracellular Ca2+ - Stebbing, Martin James; Cottee, Jennifer Marie; Rana, Indrajeetsinh (Frontiers in Immunology, 2015)
Microglia are often referred to as the immune cells of the brain. They are most definitely involved in immune responses to invading pathogens and inflammatory responses to tissue damage. However, recent results suggest microglia are vital for normal functioning of the brain. Neuroinflammation, as well as more subtle changes, in microglial function has been implicated in the pathogenesis of many brain diseases and disorders. Upon sensing alterations in their local environment, microglia change their shape and release factors that can modify the excitability of surrounding neurons. During neuroinflammation, microglia proliferate and release NO, reactive oxygen species, cytokines and chemokines. If inflammation resolves then their numbers normalize again via apoptosis. Microglia express a wide array of ion channels and different types are implicated in all of the cellular processes listed above. Modulation of microglial ion channels has shown great promise as a therapeutic strategy in several brain disorders. In this review, we discuss recent advances in our knowledge of microglial ion channels and their roles in responses of microglia to changes in the extracellular milieu.